Studies of x-ray and electron beam emissions from a low energy plasma focus / Muhammad Zubair Khan - Muhammad Zubair, Khan (2016)

(untitled)
The results of the investigation of the radiation emission (X-ray and electron emissions) from a 2.2 kJ plasma focus operated in argon are presented. Experiments were carried out using the University of Malaya-Dense Plasma Focus (UM-DPF2) device operated in argon. The charging voltage was 12 kV and the operating pressure was in the range of 0.7–2.5 mbar. Several diagnostics techniques were employed during the project, namely, high-voltage probe, five-channel PIN diode, Faraday cup, X-ray spectrometer, and scintillator–photomultiplier as detectors. In addition, the Lee model code was used to simulate the plasma focus discharge and the corresponding emission in terms of X-ray yield and electron beam fluence were analysed and compared to the measured results obtained. The main goal of our project is to conduct an in-depth investigation on X-ray emission from the UM-DPF2 device within an optimum pressure range, as well as the electron beam emission in the same pressure range. The X-ray yield, electron temperature, and electron beam fluence of argon plasma at 1.5–2.0 mbar were analysed. The charge and density of the electron beam is high at this pressure range of argon gas. The model is used to compare the results of temporal evolution and characteristics of X-ray yield and electron beam for 1.5–2.0 mbar pressure range of argon gas in the plasma focus device. The pressure 1.7 mbar of argon was found to give maximum X-ray yield and electron beam emission. A reliable low-energy plasma focus device with X-ray emission or electron beam could be used as an electron beam source in various technological fields.